2010
DOI: 10.1164/rccm.200909-1463oc
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Th17 Response in Patients with Tuberculosis Correlates with IL-6R Expression on CD4+T Cells

Abstract: Our results demonstrate that reduced Th17 responses were associated with the clinical outcome of M. tuberculosis infection. Suppression of Th17 response through down-regulation of IL-6R expression may be an important mechanism in the development of active TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
95
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 44 publications
16
95
3
2
Order By: Relevance
“…The inhibition of an M. tuberculosis-specific response has been associated with the bacterial load and the severity of the disease (11,32,53). In concordance with these studies, we found an inverse relationship between the frequency of IFN-␥-producing cells and the severity of the disease as measured by the AFB smear, although it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 86%
“…The inhibition of an M. tuberculosis-specific response has been associated with the bacterial load and the severity of the disease (11,32,53). In concordance with these studies, we found an inverse relationship between the frequency of IFN-␥-producing cells and the severity of the disease as measured by the AFB smear, although it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies reported lower mycobacteria-specific cytokineproducing peripheral blood Th17 CD4 1 T cells in TB patients compared with persons with latent TB infection. Furthermore, patients with severe TB had significantly lower Th17 response than those with mild disease (36). However, there are limited data on IL-17 in the alveolar compartment because previous studies were hampered by difficulties in detecting alveolar Th17 cells because of their very low frequencies (37) and low concentrations of IL-17 in diluted BAL fluid (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although Th17 cells have been found to be dispensable for overall protection against mycobacterial infections (4,25), IL-17-producing ␥␦-T cells do play a certain role in shaping innate and adaptive responses leading to granuloma formation (57), whereas classical (␣␤ CD4 ϩ ) Th17 cells have been associated with early and IFN-␥-independent protection (54). In humans, long-lived Ag-specific Th17 cells with a central memory phenotype and distinct from Th1 have been identified in PBMCs from healthy, mycobacterium-exposed individuals and from individuals with latent tuberculosis infection, whereas significantly reduced Th17 responses were found in patients with active TB (6,46). This correlation, with lower Th17 responses and disease progression, was not due to relocation to the lungs, as Th17 responses were found to be low to undetectable in bronchoalveolar lavage fluid and in pleural effusion from TB patients, possibly reflecting infection-mediated Th17 downregulation (6,43,46).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, long-lived Ag-specific Th17 cells with a central memory phenotype and distinct from Th1 have been identified in PBMCs from healthy, mycobacterium-exposed individuals and from individuals with latent tuberculosis infection, whereas significantly reduced Th17 responses were found in patients with active TB (6,46). This correlation, with lower Th17 responses and disease progression, was not due to relocation to the lungs, as Th17 responses were found to be low to undetectable in bronchoalveolar lavage fluid and in pleural effusion from TB patients, possibly reflecting infection-mediated Th17 downregulation (6,43,46). However, since their discovery (20,41) it has become clear that exaggerated and uncontrolled Th17 responses can be associated with autoimmunity and pathological conditions (7,9,14).…”
Section: Discussionmentioning
confidence: 99%